2013
DOI: 10.1213/ane.0b013e31824e2d37
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Mediastinal Central Line Malposition

Abstract: Central venous catheter (CVC) placement is a routine procedure in the management of critically ill patients. It is important to ensure correct positioning of the catheter tip just above the junction of the superior vena cava and the right atrium, to reduce associated complications and to optimize catheter function. The incidence of catheter misplacement is approximately 3%-4% for both subclavian and internal jugular vein access procedures. CVC placement in the right subclavian vein is associated with a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Turi reported a case of catheter placement at the anterior mediastinum, following superior vena cava perforation (5). Trunjillo described two cases of accidental placement of a central venous catheter in the left pericardiophrenic vein (6).…”
Section: Discussionmentioning
confidence: 99%
“…Turi reported a case of catheter placement at the anterior mediastinum, following superior vena cava perforation (5). Trunjillo described two cases of accidental placement of a central venous catheter in the left pericardiophrenic vein (6).…”
Section: Discussionmentioning
confidence: 99%
“…There have, however, been case reports of central venous catheter misplacement in the anterior mediastinum with vena cava perforation and even accidental placement into the intrapleural cavity [7][8]. The blood gas result confirmed that it was situated in a vein.…”
Section: Discussionmentioning
confidence: 98%
“…The blood gas result confirmed that it was situated in a vein. There have, however, been case reports of central venous catheter misplacement in the anterior mediastinum with vena cava perforation and even accidental placement into the intrapleural cavity [7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Turi et al found accidental placement of catheter in anterior mediastinum on during routine postoperative head computed tomography scan. 7 Kosmadakis et al reported a case of bilateral pleural effusion with mediastinal hematoma following misplaced tip of hemodialysis catheter in anterior mediastinum. 8 Leang et al and Kumar et al reported misplaced catheter in the pleural space.…”
Section: Discussionmentioning
confidence: 99%